Detection of viruses from patients hospitalized with lower respiratory tract infections in a public hospital, Malaysia - Musa, Siti Noorhidayah (2017)
Lower respiratory tract infections (LRTI) are among the most common human infectious diseases worldwide and responsible for a considerable number of deaths among children, particularly in developing countries. Respiratory tract infections are caused by broad spectrum microbial agents, mostly viruses and some bacteria. The common of respiratory viruses includes influenza virus A and B, parainfluenza viruses, adenoviruses, respiratory syncytial virus (RSV), rhinoviruses, and coronaviruses. In Malaysia, studies on the prevalence of these viruses are still lacking of data presentation of the virus prevalence associated with LRTI. The purpose of this study was to detect the respiratory virus aetiology from patients in Sungai Buloh Hospital, Selangor who were hospitalized with lower respiratory tract infections. A total of 210 specimens and patient’s data were collected from patients hospitalized with LRTI. The specimens were collected from April 2013 until early January 2014 after routine immunofluorescence (IF) test in hospital. Samples subjected to viral nucleic acid extraction and PCR for adenovirus, bocavirus and RSV detection. Positive PCR samples were sequenced and phylogenetic trees were constructed. Sample then analyzed based on demographic and clinical data. PCR result revealed 18 samples that were positive with adenovirus which were 11 of HAdV-7, two HAdV-1, HAdV-2 and HAdV-4 respectively and one was HAdV-5 while two positive PCR samples were HBoV1. Hospital IF test reported presence of RSV, influenza A, adenovirus, parainfluenza 3 and influenza B. Virus incidence was observed higher in children compared to adult with noticeable symptoms observed were cough, fever and difficulty of breathing, while asthma was the common underlying disease presented. Main diagnoses of the LRTI were pneumonia and bronchiolitis. In summary, viruses contribute to the etiology of LRTI among hospitalized patients in Hospital Sungai Buloh, particularly RSV followed by HAdV, influenza A, parainfluenza 3, HBoV and influenza B.